Thais França y Beatriz Padilla (eds.) Transnational scientific mobility. Perspectives from the North and from the South. Portuguese Foundation for Science and Technology (FCT), 2017 - López Fernández, Rosalía (Comparative Cultural Studies: European and Latin American Perspectives, 2018)
–